Reaction Kinetics in the Pyrolysis of Human Hair Waste - I Dewe Ketut Anom; John. Z. Lombok (Acta Chimica Asiana, 2022)
Human haircuts are a waste, and they can cause environmental problems. The human haircuts waste from barbershops has not been appropriately handled. This waste will be burned or just thrown away. Human haircut waste is difficult to decompose in nature, and the importance of environmental conservation, it is necessary to innovate in processing human haircut waste into beneficial products. This study investigates the reaction kinetics of gas formation in the pyrolysis of human hair cutting waste. The research method used is pyrolysis at high temperatures in the absence of oxygen in the system and the system under a vacuum. The pyrolysis of unwashed and washed human hair pieces follows a first-order reaction. The kinetics parameters of gas formation on the pyrolysis of unwashed human hair followed the Arrhenius equation with K= Ae-9835.1/RT, and the activation energy was 81.769x103 kJ/mol. Meanwhile, the gas kinetics on the pyrolysis of washed human hair followed the Arrhenius equation with K= Ae-3667.1/RT and the activation energy value of 30.487x103 kJ/mol.